One pot synthesis of free standing highly conductive polymer nanocomposite films: Towards rapid BTX vapor sensor. Issue 7 (4th August 2017) - Singhal, Prachi; Mazumdar, Payal; Rattan, Sunita
Abstract : In this work, we report the synthesis of robust, flexible, and free standing PMMA/NGP (nanographitic platlets) composite by one‐pot polymerization technique for sensing organic vapors. The synergy between the NGPs and PMMA matrix through strong interaction results in remarkable electrical and sensing properties of the composite system. The chemical structure and morphology of as‐prepared PMMA/NGP composites were investigated by using FTIR, XRD, and SEM techniques. The electrical conductivity of the prepared PMMA/NGP composites increases with increasing concentration of NGPs owing to the formation of conductive paths within the composite due to the quantum tunneling mechanism. The electrical conductivity of PMMA/NGP composites with different NGP concentration shows a percolation behavior with percolation threshold of ∼1.2 wt%. The temperature dependent conductivity studies of the PMMA/NGPs were studied to understand the charge transport mechanism in the composite films by using Mott's Variable range hopping model. The PMMA/NGP composite have been evaluated for detection of benzene, toluene, and xylene vapors and were found to exhibit fast response, rapid recovery, and excellent repeatability. The sensitivity along with the flexibility of PMMA/NGP composite films opens up a new opportunity to fabricate the sensor in any shape as per the requirement of modern electronics. POLYM. ENG. SCI., 58:1074–1081, 2018. © 2017 Society of Plastics Engineers